Optimization of cross-sectional shape and support parameters of headgate in fully mechanized coal seam with large dip angle and close distance - Kun PAN; Wenjun JU; Junchao WANG; Housheng JIA; Biao HOU; Yinwei WANG; Zhiming ZHANG (Meitan kexue jishu)
Aiming at the problem that the asymmetric deformation and failure of surrounding rock frequently occur, making it difficult to control the surrounding rock under the conditions of multiple intense mining actions in thecoal seam with large dip angle and close distance. Taking the headgate 31233 in Daichiba Coal Mine as the engineering background, the mechanism of surrounding rock deformation and failure in roadways with three cross-sectional shapes under thecoal seam with large dip angle and close distance was studied through theoretical analysis, numerical simulation, and on-site monitoring. The optimal asymmetric roof shaped roadway cross-sectional shape was further determined and optimized. The research results indicate that under the conditions of intense mining of steeply inclined coal seams, regardless of how the roadway cross-section changes, the form of surrounding rock failure always exhibits the maximum depth of failure towards the roof, and due to the strong stress sensitivity of the plastic zone near the upper working face area, the range and depth of the plastic zone reach a maximum, However, there are significant differences in the overall failure patterns and distribution ranges of the plastic zone among the three cross-sectional shapes. In contrast to arch roadway and inclined roof right trapezoidal roadway, the asymmetric roof shaped roadway can adjust the height of the left and right sides as well as the angles of the left and right slope tops in response to changes in surrounding rock conditions. This adjustment leads to a more rational overall stress distribution within the surrounding rock of the roadway, enhances the controllability of rock failure, and improves the utilization rate of the roadway cross-section. Based on the distribution of the plastic zone in the surrounding rock, an uneven control method is proposed, and engineering applications are conducted. The comparison of technical and economic indicators before and after optimizing the cross-section shape indicates that the uneven support method significantly improves the control over surrounding rock deformation. The research results provide an effective scientific basis for the selection of cross-sectional shapes and the optimization of support designs for similar roadways inthecoal seam with large dip angle and close distance.